Inventory and conservation plant of oke sou traditional ceremony; a welcoming tradition of maturity girl on the community of Lako Akediri Village, West Halmahera, Indonesia - ANISATU Z. WAKHIDAH; MARINA SILALAHI; DIMAS H. PRADANA (Society for Indonesian Biodiversity, 2017)
Abstract. Wakhidah AZ, Silalahi M, Pradana DH. 2017. Inventory and conservation plant of oke sou traditional ceremony; A welcoming tradition of maturity girl on the community of Lako Akediri Village, West Halmahera, Indonesia. Biodiversitas 18: 65-72. Welcoming ceremony maturity girl (oke sou) is a hereditary tradition from Lako Akediri Village which believed effective in maintaining health and beauty of girl. Oke sou ceremony held when the girl gets her first menstruation. This preliminary research aims to document plant species used in oke sou ceremonies and to explain conservation behavior of community at Lako Akediri Village towards the used plant. The investigation was conducted twice, first on May-June 2014 resumed on October 2014. Ethnobotanical data were collected using semi-structured interviews method to a village shaman, traditional elders, and local women (30 respondents). Plant specimens collected from its habitat, made herbarium, and then identified. Recorded as many as 88 plant species from 78 genera belonging to 46 families used by community at Lako Akediri Village in oke sou ceremony. Rice (Oryza sativa L.) is the most mentioned plant by the local community (20 respondents). The most widely used families are Fabaceae and Lamiaceae, each family has 7 species. The highest source of plant in oke sou ceremony derived from cultivated which in total 37 species (42%). This number represents used plants in oke sou ceremony have been widely cultivated by Lako Akediri community. The results of this study will enrich database of local knowledge in Indonesia and become source of research object in developing natural ingredients for human welfare.